Volume 11 Number 1 2015
DOI: 10.18057/ijasc.2015.11.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Tension Interaction Strength of J-Hook Connectors in Steel-Concrete-Steel Sandwich Structure

Abstract: Steel-concrete-steel (SCS) sandwich structure with ultra-lightweight cement composite core has been developed and proposed for applications in offshore, bridge and building constructions. A new form of J-hook connector is introduced to bond the steel face plates and cement composite core to form an integrated unit which is capable of resisting extreme loads. Design formulae were proposed to predict the shear, tension, and their interaction resistances of J-hook connectors. Thirty push-out tests and eighteen te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…They concluded that the code underestimates the maximum value of the shear resistance of the J-hook connectors which provide better shear transfer mechanism between concrete and steel due to their interlocking. For the applications in bridge offshore and building constructions Yan et al [5], in 2015, proposed a SCSS structure with ultra-lightweight cement composite core and J-hook connectors. They tasted 30 push-out segments and 18 tensile samples, as shown in Fig.…”
Section: Scss Push-out and Tensile Investigationsmentioning
confidence: 99%
“…They concluded that the code underestimates the maximum value of the shear resistance of the J-hook connectors which provide better shear transfer mechanism between concrete and steel due to their interlocking. For the applications in bridge offshore and building constructions Yan et al [5], in 2015, proposed a SCSS structure with ultra-lightweight cement composite core and J-hook connectors. They tasted 30 push-out segments and 18 tensile samples, as shown in Fig.…”
Section: Scss Push-out and Tensile Investigationsmentioning
confidence: 99%
“…This relative new type of structure, consisting of two faceplates and a sandwiched core, was firstly used as the undersea cylindrical shell oil containers [1]. Due to the extensive advantages received, e.g., relatively high structural performance, savings of formworks for casting, and reducing detailing works, the application of SCSSSs was gradually extended to the bridge deck [2], immersed tunnels [3], shear walls for nuclear constructions [4] and skyscraper [5], shielding tunnels [6], and protective structures against impact and blast loadings [7][8][9]. Recently, ultrahigh performance concrete (UHPC) with a compressive strength over 120 MPa has been developed and used in the SCSSSs, i.e., steel-UHPC-steel sandwich structures (SUSSSs), e.g., SUSSS developed for nuclear constructions [10] and high-rise buildings [11].…”
Section: Introductionmentioning
confidence: 99%
“…Dai et al [9] focused on the effects of concrete strength and stud collar size on the shear strength of the demountable shear connectors by experimental studies. Yan et al [10,11] investigated the mechanical behavior of J-hook connectors by push-out tests. He et al [12] tested the behaviors of the perfobond strip connector by experimental study.…”
Section: Introductionmentioning
confidence: 99%